2015
DOI: 10.1177/0883073815574334
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-Precipitating Factors in Relation to medical Recommendations

Abstract: Identification of factors precipitating epileptic seizures should always have practical implications and should always result in special recommendations given to patients. The purpose of our study is to analyze the relation between seizure-triggering factors and restrictive recommendations involving limitation of physical activity in particular. The research group consisted of 407 children hospitalized due to seizures. Their precipitants were identified in 27.5% of the patients. The most common included infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The prevalence of seizure‐precipitating factors in our study population reached 74%. This corresponds well to human questionnaire‐based studies, in which the prevalence varies between 27.5% and 98% . Furthermore, our study showed that almost all of the dogs had both precipitated and unprecipitated seizures, a finding also similar to human studies .…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of seizure‐precipitating factors in our study population reached 74%. This corresponds well to human questionnaire‐based studies, in which the prevalence varies between 27.5% and 98% . Furthermore, our study showed that almost all of the dogs had both precipitated and unprecipitated seizures, a finding also similar to human studies .…”
Section: Discussionsupporting
confidence: 91%
“…Individuals with epilepsy face barriers with respect to accessing opportunities for PA due to the perceived increased risk of seizure activity, fear of seizure-related injury and the provision of inappropriate advice from medical professionals 13,14,15 . These concerns, although persistent and pervasive, have been addressed by the International League Against Epilepsy (ILAE) Task Force Report on Sport and Epilepsy 16 which concluded that few sports should be considered off-limits for PWE, provided that appropriate, individualised risk assessment has been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Individuals with epilepsy face barriers with respect to accessing opportunities for PA due to the perceived increased risk of seizure activity, fear of seizure-related injury, and inappropriate advice from medical professionals. [13][14][15] These concerns, although persistent and pervasive, have been addressed by the International League Against Epilepsy Task Force Report on Sport and Epilepsy, 16 which concluded that few sports should be considered off-limits for PWE provided that appropriate, individualized risk assessment has been undertaken. The report also suggested that contrary to historical belief, PA may beneficially affect seizure frequency and severity and that PA is unlikely to provoke seizure activity even when intensity of physical effort is increased to a point of exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…As for the seizures episode, we know that infections and fever are leading seizure-precipitating factors in children. (6) To our knowledge, this is the rst case of self-limited seizures in an afebrile child with SARS-CoV-2. At present, we can only speculate that SARS-CoV-2 infection may have triggered the onset of selflimited focal epilepsy in our patient.…”
Section: Resultsmentioning
confidence: 80%